Identidad juvenil femenina a partir de marcas de moda en instagram - Purizaga Yactayo, Alexandra Iliana (2022)
In recent years, the consumption of social networks by young people has increased greatly. Facebook, Twitter and Instagram are among the main platforms that have a great impact on the process of identity formation, since the content that is consumed, whether positive or negative, cannot be controlled. However, of the networks mentioned above, the one with the largest number of users is Instagram, and it is also commonly used by youth fashion brands, since this social network allows you to publish only audiovisual content, achieving a greater reach and increasing the visibility of brands. . That is why this research work seeks to analyze how the identity of young Peruvian women is constructed from the audiovisual content generated by fashion brands on Instagram. The study is framed within the qualitative approach, with the semi-structured interview being the instrument used to collect information.